2013
DOI: 10.13189/ujps.2013.010306
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Micropropagation of the Ornamental Plant Dieffenbachia-A Review

Abstract: Ornamental industry has applied immensely in vitro propagation approach for large-scale plant multiplication at very high rates of elite superior varieties. As a result, hundreds of plant tissue culture laboratories have come up worldwide. Dieffenbachia species are popular foliage potted plants used in interiorescapes of homes, offices, and malls throughout the world. Most of Dieffenbachia species are now propagated by tissue culture for better utilize of species and expedite plant improvement. This review pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Gladiolus plant micropropagation, in vitro cormel production, and gladiolus improvement through biotechnological techniques are all dependent on a number of factors, including genotype, culture media, and environmental factors [43]. The type of plant or stage of life of the donor plant determines how the culture is implemented [44]. A range of elements, including light, temperature, humidity, and carbon dioxide, influence the morphology and physiology of mature in vitro plants [45].…”
Section: Gladiolus In Vitro Propagation: Advantages and Applicationsmentioning
confidence: 99%
“…Gladiolus plant micropropagation, in vitro cormel production, and gladiolus improvement through biotechnological techniques are all dependent on a number of factors, including genotype, culture media, and environmental factors [43]. The type of plant or stage of life of the donor plant determines how the culture is implemented [44]. A range of elements, including light, temperature, humidity, and carbon dioxide, influence the morphology and physiology of mature in vitro plants [45].…”
Section: Gladiolus In Vitro Propagation: Advantages and Applicationsmentioning
confidence: 99%
“…Petal explants of P. tuberose was implemented to initiate globular and heart somatic embryos that after 3 weeks developed as torpedo and cotyledonary embryos. Axillary branching using axillary bud and stem node, as in other plants, is the majority common explants type utilized for direct shoot propagation of Dieffenbachia [74]. The majority of the strategies established for in vitro multiplication of Phalaenopsis include seedling propagation or cultured the dormant buds located at the base of the inflorescence.…”
Section: Type Of Explantsmentioning
confidence: 99%
“…Plant micropropagation is one of the best alternatives for crop improvement and shows a special significance in multiplication through a vegetative approach. This minimizes the risk of pathogen accumulation and the slow proliferation rate in generative multiplication, which in turn, causes a loss in both crop quantity and quality [39][40][41][42]. Several studies have shown the positive impacts of AgNP augmentation for callus induction, shoot generation, and growth (Table 1).…”
Section: Silver-nanoparticles In Crop Improvementmentioning
confidence: 99%